PENINGKATAN KUALITAS PRODUK GULA KELAPA SEMUT SEBAGAI PRODUK POTENSI EKSPORT DARI KABUPATEN BANYUMAS - Agus Suroso; Ascaryan Rafinda; Negina Kencono Putri (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
The specific objectives and targets of this PkM activity are; Improving quality control of raw materials and production processes; Product quality improvement; Provision of production equipment facilities in the form of drying ovens to improve production quality and Assistance and improvement of partner business management. The approach used to overcome the problems faced by partners is the method of training, introduction, and application of appropriate technology, counseling and mentoring. The activity plan in the proposed PkM program includes; 1) Training on the technique of making ant sugar, 2) Technical training on using a drying oven, 3) Introduction and transfer of technology in the form of ant sugar drying oven, 4) Assistance in efforts to increase HR competency in terms of financial administration and quality management. The targeted outputs of this PkM activity are 1) The group has machine-based production equipment, 2) The group has better product packaging, 3) The group has more structured quality management capabilities, an established marketing strategy, and more organized financial administration.